University Student Responses to Ethical Violations on Social Media: A Case Study from Banggai Regency - Aquarini; Suffianor; Yopiannor, Farid Zaky (Yayasan Sinergi Kawula Muda, 2025)
In the rapidly evolving digital landscape, university students increasingly confront ethical violations on social media platforms, ranging from privacy breaches to cyberbullying and misinformation. This study investigates how students in Banggai Regency, Indonesia, perceive and respond to unethical content encountered online. Employing a qualitative descriptive approach, data were collected through in depth interviews and digital observations with active social media users across multiple platforms. Thematic analysis guided by Miles and Huberman’s model revealed that students employ a combination of cognitive appraisal and avoidance strategies, including skipping, unfollowing, reporting, blocking, and content filtering, to navigate unethical digital environments. Findings highlight the role of psychological resilience, digital literacy, peer norms, and platform design in shaping student behaviors. Furthermore, student led initiatives such as digital ethics campaigns and peer fact checking groups emerged as critical interventions promoting responsible digital engagement. These insights underscore the transformative potential of youth agency in fostering ethical online cultures. The study contributes to the broader discourse on digital citizenship by emphasizing the need for integrated digital ethics education and collaborative policy interventions.